Building Modern Banking Solutions: A Technical Guide to .NET Implementation in U.S. Financial Services - Veera Venkata Ramana Murthy Bokka, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive technical article explores the implementation of .NET technology in modern U.S. banking systems, focusing on the digital transformation of financial services. The article examines how financial institutions leverage .NET's robust framework to develop scalable, secure, and efficient banking solutions. It investigates core banking architecture, essential product development, cloud integration strategies, security frameworks, and future technological considerations. It demonstrates how .NET's cross-platform capabilities and extensive ecosystem enable banks to create sophisticated applications while maintaining regulatory compliance. The analysis encompasses various aspects of banking technology, including payment processing systems, fraud detection mechanisms, customer analytics platforms, and cloud-based solutions. The article also addresses the critical role of security and regulatory compliance in modern banking systems, highlighting how institutions implement comprehensive security frameworks and automate compliance processes. Furthermore, it explores the evolution of development tools and future considerations, emphasizing the importance of API-first strategies, microservices architecture, and sustainable maintenance planning in the banking sector.
Keywords: Digital Banking Transformation; .NET Framework Architecture; Cloud Integration; Banking Security Compliance; Microservices Development